THE EFFECT OF PROBIOTIC ADDITION IN FEED TOWARDS GROWTH PERFORMANCE AND SURVIVAL RATE OF TAMBAQUI (Colossoma macropomum) USING BIOFLOCS SYSTEM - Wirangga Albab Abrar; Niken Ayu Pamukas; Iskandar Putra (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTThis research aim to determine the optimal dose of additional probiotic in feed toward the growth performance and survival rate of tambaqui (Colossoma macropomum) by using biofloc system. This research was conducted on March 30-May 9, 2018 at Technical Service Unit (UPT) of Hatchery, Marine and Fisheries Faculty, University of Riau. This research was using experimental method by completely random design (RAL) one factor with three replications. The treatments were: A: 0 g/kg of feed (control), B: 0,5 g/kg of feed, C: 1 g/kg of feed, and D: 2 g/kg of feed. The probiotic (Bacillus sp) The results showed that a different doses of additional probiotic affecting the growth performance and the survival rate of tambaqui using biofloc system. In addition, it also affected the absolute weight growth, absolute length growth, feed efficiency and feed conversion ratio.The optimal dose was at 2 g/kg of feed as it showed significantly different results compared to control and was not differ significantly at higher doses. So that while being applied in terms of economy, 2 g/kg was the most efficient dose, by giving the absolute weight growth was 37,62 g, absolute length was 6,91 cm, specific growth rate was 7,00%, feed efficiency was 104,16%, feed conversion ratio was 0,96 and survival rate was 100%.Keyword : probiotic, tambaqui, biofloc